The Comparative Analysis of Higher School Students’ Conflictological Culture On The Basis Of Their Left-/Right- Handedness - Shsherbakova, Olga; Tatarinceva, Anna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
We face with different kinds of conflicts every day. The problem of the conflictological culture   of personality is urgent nowadays, because only a person with a highly developed level of the ability to avoid or successfully solve conflicts can succeed at work and in life-long learning. The European Council defined five key competences necessary for future specialists’ successful functioning in the contemporary society. The first place in this list was assigned for social competence as the ability to be responsible, able to take part in group decisions, avoid and resolve conflicts (The Symposium of the European Council. Brussels, 1996). The authors of the given research analyze the essence of the notions ”conflict”,  “conflictological culture”, as an integral quality of a person where the main stress is paid on its structural components’ content. They also  investigate different aspects of activities and psychophysiological development of left- and right-handedness of people. The empirical analysis conducted in the research presents the data obtained in the investigation  of the left- and right-handed students’ conflictological culture’s level. The Object of the research is the conflictological culture’s  level of students  at higher school. The Aim of the research is to investigate: 1) the essence of  the notions “ conflict”, “ conflictological  culture”, 2) the level of conflictological culture  of students of the 1st and 4th courses at  higher school on the basis of their left-/right—handedness. The Methods of the research are the following:1. Theoretical methods:The theoretical analysis of scientific literature on the given problem.2.Quantitative methods: questionnaires.3.The empirical analysis of obtained data.